Social Comparisons and Need Fulfillment: Interpreting Video Game Enjoyment in the Context of Leaderboards. Issue 5 (20th October 2018) - Velez, John A.; Ewoldsen, David R.; Hanus, Michael D.; Song, Hyunjin; Villarreal, Jonathan A.
Abstract : This study examines how social comparison information provided by video game leaderboards may influence players' retrospective judgments of autonomy, competence, and relatedness need fulfillment. Participants played a video game and were randomly assigned to receive no postgame feedback or were shown a leaderboard that placed them in the top or bottom quartile of players. Results indicate downward social comparisons increase enjoyment by increasing competence and relatedness perceptions. However, upward comparisons did not have an opposite effect, nor did either type of social comparison influence players' autonomy perceptions. Implications for applying Self-Determination Theory to video game enjoyment in the context of social comparison feedback is discussed.